معاصر تانیثی نظم کے تین ابعادثمینہ راجہ،یاسمین حمید،حمیدہ شاہین - Muhammad Imran Azfar (Khayaban - خیابان, 2022)
ABSTRACT: Feminism is about all genders having equal rights and opportunities. It's about respecting diverse women's experiences, identities, knowledge, strength, and striving to empower all women to realise their full rights. Feminist literature is fiction or poetry which supports the feminist goals of defining, establishing, and defending equal political, economic, and social rights for women among man based socio political scenario.This article argues about the three prominent feminist poet's in Urdu poem. These three Samina Raja, Fehmida Riaz and Kishwar Naheed are the first line creator's in our Society. In this article selective text of these creator's identified in light of feminist theory.